Digitalisasi UMKM: Peningkatan laporan keuangan menggunakan Lamikro dan strategi pemasaran - Andari, Atik Tri; Setianingsih, Novie Astuti; Asmoro, Wiwiek Kusumaning; Putranti, Eti; Sari, Hanifah Puspita; Fitriani, Dwi Rahma (Nur Science Institute, 2024)
The role of MSMEs in the Indonesian economy is very large, so the government encourages the MSME sector to develop more rapidly. One of the MSMEs in Kediri Regency is the MSME Jajan Gimbul Ibu Azma which is engaged in the culinary fields of siomay, tofu meatballs, and cilok. The financial records of partners are still in manual form in the form of income and expenses that are not yet regular, so that financial developments are less clearly visible. In addition, in carrying out marketing, partners still do not utilize social media. Therefore, the purpose of this assistance is to improve the skills of MSME owners to create financial reports using the Lamikro application and marketing assistance through social media. The implementation method consists of team coordination, team coordination with partners, training in recording financial reports using the Lamikro application, marketing training using social media, and evaluation. The results of this program show that there is an increase in partners in recording financial reports using the Lamikro application. In addition, the next result is an increase in partners in marketing through social media, namely Instagram. It can be said that partners have succeeded in improving financial report recording and conducting online marketing well.